Atlantic Union Committee records - Atlantic Union Committee; Head, Henry William Nugent, 1898-1964.
Correspondence, memoranda, minutes, reports, financial records, office administrative files, chapter files, clippings, printed materials, and other records relating primarily to the organization and activities of the committee, chapter activities, and resolutions submitted to the U.S. Congress. Includes the papers of Henry William Nugent Head pertaining chiefly to his role in the committee's efforts to establish an overseas base. Correspondents include Herbert Agar, Robert J. Bishop, Justin Blackwelder, Will Clayton, Lionel Curtis, Donald P. Dennis, C.A. Edson, Henry C. Flower, Ellen Garwood, Guy M. Gillette, Livingston Hartley, Gerald B. Henry, Hubert H. Humphrey, Irving McNeil Ives, Lyndon B. Johnson, Estes Kefauver, Edward J. Meeman, Hugh Moore, Walden Moore, Edmund Orgill, Stellanova Osborn, Lithgow Osborne, Robert Porter Patterson, Owen J. Roberts, Elmo Roper, and Clarence K. Streit.
Organization promoting the establishment of a federal union of European and North American democracies. Formed in 1949; dissolved in 1961.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Agar, Herbert, -- 1897-1980 -- Correspondence; Bishop, Robert J. -- 1913- -- Correspondence; Blackwelder, Justin -- Correspondence; Clayton, Will, -- 1880-1966 -- Correspondence; Curtis, Lionel, -- 1872-1955 -- Correspondence; Dennis, Donald P. -- 1916- -- Correspondence; Edson, C. A. -- Correspondence; Flower, Henry C. -- Correspondence; Garwood, Ellen, -- 1903- -- Correspondence; Gillette, Guy M. -- 1879-1973 -- Correspondence; Hartley, Livingston, -- 1900- -- Correspondence; Henry, Gerald B. -- Correspondence; Humphrey, Hubert H. -- 1911-1978 -- Correspondence; Ives, Irving McNeil, -- 1896-1962 -- Correspondence; Johnson, Lyndon B. -- 1908-1973 -- Correspondence; Kefauver, Estes, -- 1903-1963 -- Correspondence; Meeman, Edward J. -- 1889-1966 -- Correspondence; Moore, Hugh, -- 1887-1972 -- Correspondence; Moore, Walden -- Correspondence; Orgill, Edmund -- Correspondence; Osborn, Stellanova, -- 1894-1988 -- Correspondence; Osborne, Lithgow, -- 1892-1980 -- Correspondence; Patterson, Robert Porter, -- 1891-1952 -- Correspondence; Roberts, Owen J. -- 1875-1955 -- Correspondence; Roper, Elmo, -- 1900-1971 -- Correspondence; Streit, Clarence K. -- 1896-1986 -- Correspondence; United States. -- Congress -- Resolutions; International organization; Internationalism -- Societies, etc